2019
DOI: 10.2147/idr.s219155
|View full text |Cite
|
Sign up to set email alerts
|

<p>High rate of multiresistant <em>Klebsiella pneumoniae</em> from human and animal origin</p>

Abstract: Purpose The main objectives of the present study were to detect the antimicrobial susceptibility and molecular characteristics of Klebsiella pneumoniae isolated from different hosts and to investigate the possibility of K. pneumoniae transmission between animals and humans. Materials and methods A total of 189 nonduplicate K. pneumoniae isolates were collected from hospitals and four specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 46 publications
6
29
1
1
Order By: Relevance
“…In this study, K. pneumoniae was isolated from 9% of diseased chickens and 16.7% of environment samples, which is inconsistent with the findings reported in a previous study in Egypt, where K. pneumoniae was recovered from 35% of broiler chickens and 25% of water samples [ 42 ]. However, the prevalence of K. pneumoniae among contact poultry workers (22.7%) and hospitalized patients (14.4%) in the same region was lower than lately published reports in Egypt [ 7 , 42 , 43 ] or abroad, both in China [ 44 ] and Taiwan [ 45 ]. Hence, the direct transmission may be facilitated via close contact between chickens and humans as evidenced previously by Davis et al [ 46 ].…”
Section: Discussionmentioning
confidence: 62%
“…In this study, K. pneumoniae was isolated from 9% of diseased chickens and 16.7% of environment samples, which is inconsistent with the findings reported in a previous study in Egypt, where K. pneumoniae was recovered from 35% of broiler chickens and 25% of water samples [ 42 ]. However, the prevalence of K. pneumoniae among contact poultry workers (22.7%) and hospitalized patients (14.4%) in the same region was lower than lately published reports in Egypt [ 7 , 42 , 43 ] or abroad, both in China [ 44 ] and Taiwan [ 45 ]. Hence, the direct transmission may be facilitated via close contact between chickens and humans as evidenced previously by Davis et al [ 46 ].…”
Section: Discussionmentioning
confidence: 62%
“…K. pneumoniae is a nosocomial pathogen with increasing MDR rates and global dissemination of high risk clones [ 70 ]. Although several studies have previously focused on K. pneumoniae in farm and companion animals [ 71 , 72 , 73 , 74 ], information about this pathogen in wildlife is still scarce [ 42 , 55 , 75 , 76 , 77 , 78 ]. Nevertheless, there are some reports about the isolation of K. pneumoniae from marine mammals along the U.S. Pacific Coast [ 19 , 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although pathogens resistant to only one antibiotic may cause severe infections that are very hard to treat, MDR bacteria, such as those isolated from cattle feces, are particularly dangerous. Yang et al (2019) identified MDR in ESBL + K. pneumoniae isolated from cow feces. The strain showed resistance to 13 antibiotics from almost all commonly-used antimicrobial classes.…”
Section: The Use Of Antibiotics In the Cattle Industry And Its Effect On The Cattle Manure Resistomementioning
confidence: 99%